Job satisfaction related with organizational commitment: a study on bank employees at northern region / Kamarul Azman Khamis, Ramli Saadand Daing Maruak Sadek - Khamis, Kamarul Azman; Saad, Ramli; Sadek, Daing Maruak (2011)
The purpose of this paper is to empirically examine the extent to which job satisfaction correlate with organizational commitment focusing on bank employees specifically and private sector generally. The study also tries to identify the strongest variables of job satisfaction that contribute towards organization commitment. A sample of 200 respondents was randomly chosen in this survey which 150 respondents gave the feedback. Correlation and regression analysis are being used to determine the relationship between job satisfaction variables (company policy, salary, working condition, interpersonal relation and advancement) and organizational commitment. The result from hypotheses testing has shown that all independent variables have positive relationship with organizational commitment. Furthermore, the result on regression also shows that advancement has the strongest relationship with organizational commitment compare to other variables. As a conclusion, we do believe that the results could be used by organizations to increase their employees’ commitment and lead to further research in the future